ERA5.1: Corrections to ERA5 Stratospheric Temperature 2000-2006 ... - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2020)
In ECMWF Technical Memo 859 released in January 2020, Simmons and his coauthors report that "the ERA5 analyses of lower stratospheric temperature exhibit a pronounced cold bias for the years 2000 to 2006. This is due to specifying background error covariances for the data assimilation that were inappropriate prior to availability during 2006 of GNSS radio occultation data in sufficient numbers to constrain a cold bias of the assimilating ERA5 model. A new set of analyses, termed ERA5.1, has thus been produced for the period from 2000 to 2006 using the background error covariances that were used to produce the ERA5 analyses for the years 1979 to 1999. ERA5.1 also includes the more restrictive ensemble assimilation of SBUV ozone data that was used in production of ERA5 for 1979 to 1999.""ERA5.1 provides analyses with better global-mean temperatures in the stratosphere and uppermost troposphere than provided by ERA5. ERA5.1 stands up well in comparison with ERA-Interim and other reanalyses in the lower ...